Efficacy of Copper Ion Treatment on Bacteria and Antibiotic Residues Contained in Bovine Waste Milk - Fernando Ulloa; Martina Penati; Constanza Naegel; Carlos Tejeda; Miguel Hernández-Agudelo; Pamela Steuer; Miguel Salgado (MDPI AG, 2024)
Background/Objectives: Waste milk harbors many bacteria and antibiotic residues. Calves fed with untreated waste milk have a higher incidence of scours and an increased risk of developing antimicrobial-resistant bacteria. This study aimed to evaluate the efficacy of treatment with copper ions on bacteria and antibiotics contained in bovine waste milk. Methods: Waste milk samples were collected from a dairy farm for seven weeks and were subjected to treatment with copper ions. Total bacterial counts, coliforms, Streptococcus, and Staphylococcus were assessed before and after treatment. Additionally, metagenomic analysis was performed to determine microbial diversity. Results: Before treatment, the total bacterial count average was 4.0 × 106 CFU/mL, 1.7 × 104 CFU/mL for coliforms, 2.6 × 106 CFU/mL for Streptococcus, and 5.4 × 102 CFU/mL for Staphylococcus Copper treatment significantly reduced bacterial counts within 15 min. Total bacteria decreased from 4.0 × 106 CFU/mL to 1.1 × 102 CFU/mL after 30 min; meanwhile, other groups were not detected. The most abundant groups were Lactococcus (29.94%), Pseudomonas (28.89%), and Enterobacteriaceae (21.19%). Beta-lactams were detected in five-sevenths samples, and in one sample they were detected before and at 15 min of treatment but not after 30 min. Conclusions: The effect of treatment with copper ions on the different bacterial groups was significantly effective but showed limited effect on the detection of antibiotics.